Social Media as a Negative Source of Political News in a Polarized Society? Indonesian and Filipino Students' Perception - Titin Setiawati; Andys Tiara; Sri Mustika (Program Studi Ilmu Komunikasi, 2023)
The polarized society due to political elections in Indonesia and the Philippines is inseparable from many aspects. This study aims to elaborate the perception of Indonesian and Filipino students of social media as a political news source in a polarized society during the Covid-19 pandemic. This study uses a qualitative method. The result of this study shows that Indonesian and Filipino students used social media as a reference news source. For Indonesian students, Instagram became the most influential social media, whilst for the Filipino students, Facebook was the most influential social media. Indonesian students negatively perceived social media as a political news source due to the power of social media to increase or decrease polarization, whereas Filipino students have a reversed point of view. The positive perception of media is related to the ability of social media to give the knowledge about the political actors. According to Indonesian and Filipino students, political polarization in society occurs and continues because it is caused by fanaticism, group influence and the media. This research provides new insights to the public about how social media can affect social conditions concerning political contestation, and provides insight to political contestants about the social media usage as a source of political news among the younger generation.